Analysis of the Success Factors of the Blended Learning, Learning System at XYZ University (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Technology is currently developing very rapidly. Many things can be done now thanks to highly developed technology. Education also develops in line with technology, thanks to the internet now students can learn on their own from wherever and whenever they want. By utilizing the advantages of the internet, we now have a Blended Learning system that combines the advantages of a face-to-face learning system with an online learning system. This paper will discuss the application of the Blended Learning system at one of the best universities in Indonesia. This paper will examine what factors influence the success in implementing the learning system in universities.